A review of Rheosmittia Brundin, 1986 (Diptera: Chironomidae) from China based on DNA barcodes and morphology - Zhang, Zhi-Chao; Chen, Yi-Zhu; Zhang, Yan; Yao, Yuan; Lin, Xiao-Long (Zootaxa, 2026)
Rheosmittia Brundin, 1986 (Diptera: Chironomidae) from China is reviewed based on DNA barcodes and morphology. Two new species, Rheosmittia motuoensis Zhang & Lin, sp. nov. from Xizang and Rheosmittia wangi Zhang & Lin, sp. nov. from Yunnan, as well as an unidentified larva from Zhejiang, are described and illustrated. The first new species is characterized by its distinctive body coloration, smaller AR, and inferior volsella positioned at the midlength of the gonocoxite, while the second new species is distinguished by slightly curved gonostylus and longer costa extension. Given the distinctive morphology of the gonostylus in R. wangi within the genus, generic diagnosis is amended. A key to adult males of extant Rheosmittia is presented.